The Existence of Customary Law: Badamai Customary Law - Ahmad Syaufi; Aurora Fatimatuz Zahra; Mursidah (Research Horizon, 2021)
Adat badamai is one form of dispute resolution commonly carried out by the Banjar people. Adat Badamai is also meant as a result of the process of deliberation in the discussion together with the intention of achieving a decision as a solution to a problem. Adat Badamai is done in order to avoid disputes that can endanger the social order. This study aims to determine the existence of Badamai Customary Law in Banjar Community, Kalimantan. The study was conducted by using socio-legal approach in analyzing the role of modern regulation with the customary practices. results showed that the existence of customary law in South Kalimantan in the Banjar tribe community is a reality that can be found in the people of Banjar people in South Kalimantan, known as the Badamai custom. Adat Badamai is done in order to avoid disputes that can endanger the social order. The Badamai decision produced through the mechanism of deliberation is an alternative effort in finding a way out to solve problems that occur in society. In the Banjar community if there is a dispute between residents or acts of persecution or violation of norms (adat) or fights or traffic violations, then the community tends to resolve in a customary-based manner.